THE EFFECTIVENESS OF USING AN ASIAN PARLIAMENTARY DEBATE TECHNIQUE TO IMPROVE STUDENTS’ SPEAKING SKILLS - Irkhamna Fitriarrum; Mukminatus Zuhriyah (J-Shelves of Indragiri (JSI), 2025)
Speaking skills are essential for effective communication and play a significant role in academic achievement, especially in the context of learning English as a foreign language. However, many students face difficulties in fluency, pronunciation, and confidence when speaking English. Traditional teaching methods often fail to sufficiently enhance students’ speaking skills, necessitating the exploration of more interactive approaches such as debate. This research investigates the effectiveness of using debate technique to improve the speaking skills of class XI A at a private Islamic school in Ngemplak area. This study applies a pre-experimental design with a one-group pre-test and post-test model. A total of 26 female students were selected as participants using purposive sampling, considering institutional regulations. The research process consisted of three phases: an initial assessment (pre-test) to evaluate students’ speaking skills, an intervention stage where the debate technique was applied, and a final assessment (post-test) to measure the improvement. Data were analyzed using descriptive statistics and paired sample t-tests. The results reveal a significant enhancement in students' speaking performance following the debate technique application. The mean score of the post-test (77.88) showed a notable increase compared to the pre-test score (61.92), with statistical analysis confirming a significant difference (p < 0.05). This finding suggests that the debate technique is effective to improving students' fluency, pronunciation, vocabulary, and confidence in English communication. In summary, incorporating debate as a learning method allows students to develop structured argumentation, strengthen critical thinking, and engage in interactive discussions. Educators are encouraged to integrate debate techniques more frequently to maximize speaking practice. Further research should consider other influencing factors and extend the study duration to optimize students' learning outcomes.